Cost Effectiveness of Whole Exome Sequencing for Children with Developmental Delay in a Developing Country: A Study from Jordan - Masri, Amira; Hamamy, Hanan (Journal of Pediatric Neurology, 2021)
This retrospective study aimed to determine the cost effectiveness of whole exome sequencing (WES) in the diagnosis of children with developmental delay in a developing country. In this study of 40 patients, the average cost of traditional investigations and indirect costs related to rehabilitation and medications per child were USD847 and 6,585 per year, respectively. With a current cost for WES of approximately USD1,200, we concluded that performing WES could be cost effective, even in countries with limited resources, as it provides the option for genetic counseling in affected families with an ultimate reduction of overall financial burden to both parents and health care system.
Keywords: whole exome sequencing; developmental delay; Jordan